EVALUASI TINGKAT PENERAPAN TEKNOLOGI BUDIDAYA TANAMAN PADI SAWAH DI KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Wely Yitro Pello; Basry Yadi Tang (Partner, 2020)
The purpose of this study was to evaluate the application level of paddy rice cultivation technology in East Kupang Sub-district. The study was conducted at the Agricultural, Fisheries and Forestry Counseling Agency (BP4K), East Kupang District.The results showed that: The level of application of paddy cultivation technology in East Kupang District was in the High category with a value of 58.34%, an Achievement Score of 32.90 and a percentage of achievement of 82.29%. Keywords: Application, Technology, Paddy Rice